Glutamate 270 plays an essential role in K+‐activation and domain closure of Thermus thermophilus isopropylmalate dehydrogenase. Issue 2 (10th December 2014) - Gráczer, Éva; Palló, Anna; Oláh, Julianna; Szimler, Tamás; Konarev, Petr V.; Svergun, Dmitri I.; Merli, Angelo; Závodszky, Péter; Weiss, Manfred S.; Vas, Mária
Abstract : The mutant E270A of Thermus thermophilus 3‐isopropylmalate dehydrogenase exhibits largely reduced (∼1%) catalytic activity and negligible activation by K + compared to the wild‐type enzyme. A 3–4 kcal/mol increase in the activation energy of the catalysed reaction upon this mutation could also be predicted by QM/MM calculations. In the X‐ray structure of the E270A mutant a water molecule was observed to take the place of K + . SAXS and FRET experiments revealed the essential role of E270 in stabilisation of the active domain‐closed conformation of the enzyme. In addition, E270 seems to position K + into close proximity of the nicotinamide ring of NAD + and the electron‐withdrawing effect of K + may help to polarise the aromatic ring in order to aid the hydride‐transfer. Abstract : The role of a conserved residue (E270) of 3‐isopropylmalate dehydrogenase has been determined. The mutant E270A exhibits largely reduced catalytic activity and negligible activation by K + . QM/MM calculations predicted an increase in the activation energy of catalysis upon the mutation. The X‐ray structure of the E270A mutant exhibited a bound water molecule in the place of K + . SAXS and FRET experiments revealed the role of E270 in domain‐closure required by the function.